PENGARUH PERSENTASE MALTODEKSTRIN DAN LAMA PENGERINGAN TERHADAP KANDUNGAN VITAMIN C MINUMAN SERBUK INSTAN TERONG CEPOKA (Solanum torvum) - Karimatus Sakdiyah; Rekna Wahyuni (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2019)
Cepoka eggplant (Solanum torvum) which has a bitter taste when consumed is less attractive to the public even though its properties are good for health. This study aims to determine the effect of maltodextrin percentage and drying time on vitamin C content of instant powdered eggplant cepoka. The method used in the research of instant eggplant cepoka powder is Factorial Randomized Block Design (RBD) which consists of 2 factors: maltodextrin composition (10%, 20%, and 30%) and drying time (6 hours and 7 hours). Each study was repeated 3 times so that 18 trials were obtained. Tests carried out include physicochemical (vitamin C test, water content test, soluble speed test) and organoleptic test (color, aroma, and taste). Data analysis is done by ANOVA. If it is significantly different, then it is continued by using the Smallest Significant Difference Test (BNT), organoleptic test using Friedman and to find the best treatment using the De Garmo Effectiveness Index (1984) method modified by Susrini (2003). The best results were found in the treatment of 30% maltodextrin and 7 hours drying time (M3P2) with the following results: KA (8.58%), Soluble Speed ​​(0.34s), Vitamin C (28.75mg/g), panelist's preference for 3.55 powder color (neutral / normal), 3 beverage color (neutral / normal), 2.65 (not liking) the drink aroma, and 2.85 (not like) the taste of the drink.